Micro Level Assessment of Water Resources in Bist Doab Tract of Indian Punjab - Aggarwal, Rajan; Kaur, Samanpreet; Juyal, Dhruv (Journal of Agricultural Engineering, 2009)
Water is a vital input in agriculture and has made significant contribution in providing stability to food grain production and self-sufficiency. The resource can be optimally used and sustained only when quantity of water is assessed at micro level. The present study was aimed to estimate the gap in demand and supply of water resources at the Block level during Kharif and Rabi season in Bist Doab tract. The average total annual water demand was found to exceed the average annual available water by 255,996 ha.m; 145,945 ha.m (57%) in Kharif and 110,052 ha.m (43%) in Rabi season. The highest water deficit of 543 mm in Mukerian Block and of 231 mm in Balachur Block were observed in Kharif and Rabi season, respectively. The analysis revealed that the rice-wheat cropping system is the major factor responsible for higher water demand leading to water deficit in the Bist Doab tract.